Translation Studies and Representative Corpora: Establishing Links between Translation Corpora, Theoretical/Descriptive Categories and a Conception of the Object of Study - Halverson, Sandra (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractThis paper discusses the issue of representativeness in the creation of general translation corpora. In the course of a in-depth examination of the stages involved in the selection of texts which adequately represent the target population, it demonstrates that prototype categories are better suited than the all-or-none classical ones to reconcile existing theoretical statements about what constitutes legitimate data in translation studies with the new methodology developed by the corpus-based approach.